Determination of Optimum Rate of Nitrogen and Sulphur Application for Sesame (Sesamum Indicum L.) Production in Ibadan and Ogbomoso, Nigeria - Omogoye, Adewale Mubo; Akinrinde, Ezekiel Akinkunmi; Akinrinola, Tajudeen Bamidele (Agricultural Development, 2025)
Sesame is a high-valued crop grown for its oil and protein-rich edible seed, which requires Nitrogen (N) and sulphur (S) for biosynthesis of oil and protein, and optimum seed production and nutritional content. In a 2×4×3 factorial arrangement fitted in completely randomised design with four replicates, sesame varieties E8 and NCRIBEN-01M were grown on 6 kg soil/pot with nitrogen at N0, N60, N90 and N120 kg N/ha (using urea) in combination with sulphur at S0, S30 and S60 kg S/ha (through magnesium tetra oxo sulphate VI) in screenhouses at Ibadan and Ogbomoso, Nigeria. Data were collected on plant height, stem diameter, seed weight, and seed N and S contents. Seed weight (g/plant) was used as benchmark for determining optimum N and S application rates on polynomial regression curves, which were obtained at points where second derivatives (d2y/dx2) of regression equations turn to zero. In Ibadan and Ogbomoso, seed weight ranged from 1.90±0.04 (N0×S0×E8) to 2.60±0.04 (N120×S60×NCRIBEN-01M) and 2.1±0.05 (N0×S0×E8) to 2.8±0.05 (N120×S60×NCRIBEN-01M), respectively. The seed weight of 2.6 g/plant (N90×S30×NCRIBEN-01M-Ibadan) and 2.7 g/plant (N90×S30×NCRIBEN-01M-Ogbomoso) were the optimum seed yields, while the optimum rates of nitrogen were 89 kg/ha (R2= 0.71) and 88 kg/ha (R2= 0.78) in Ibadan and Ogbomoso locations, respectively. Optimum S rates were 30.8 kg/ha (R2= 0.92) and 33.0 kg/ha (R2= 0.97). Therefore, 90 kg N/ha + 35 kg S/ha could be adopted as N-S application rate at Ibadan and Ogbomoso.